Predictors of death in hospitalized elderly patients with COVID-19 in Mashhad, Iran, in 2021: A historical cohort study - Vajihe Biniaz; Alireza Afshari Safavi; Forogh Zamani; Mozhgan Rahnama; Abdolghani Abdollahimohammad; Eshagh Ildarabadi (Wolters Kluwer Medknow Publications, 2023)
Objective: The present study aimed to identify predictive factors for mortality among elderly individuals infected with COVID-19. Methods and Materials: This historical cohort study was conducted from July to December 2021 in the specialized departments for COVID-19 patients at one of the hospitals in Mashhad, Iran. Data were collected from the medical records of 404 elderly patients. Sampling was conducted using the convenience sampling method. Data were gathered through a demographic and clinical checklist developed by the researcher. Univariate and multivariate Cox regression were used to analyze the data. Results: The mortality rate among elderly individuals was 25% (n = 101). Multiple regression analysis revealed significant associations between mortality and age (hazard ratio [HR] = 0.58, 95% confidence interval [CI]: 0.38, 0.88; P = 0.011), level of consciousness (HR = 0.31, 95% CI: 0.19, 0.50; P < 0.001), and SpO2 (HR = 0.58, 95% CI: 0.37, 0.92; P = 0.022). The probability of survival after the 19th day of hospitalization was 50%. Conclusions: Determining predictors of death allows for early identification of elderly individuals at risk and enables the health-care team to provide more effective care, ultimately saving the lives of elderly individuals by allocating appropriate facilities and equipment.